Long term trends in abundance of humpback whales in Hervey Bay, Australia - H. Forestell, Paul; D. Kaufman, Gregory; Chaloupka, Milani (J. Cetacean Res. Manage., 2020)
Seasonal abundance estimates of humpback whales resident during the austral winter in Hervey Bay, Queensland, Australia between 1987 and 2007 were obtained from a capture-mark-recapture study using photo-identification images of 3,155 individual whales. Hervey Bay is a major southbound stopover site for Breeding Stock E humpback whales returning to Antarctic waters from over-wintering in the vicinity of the Great Barrier Reef. Annual survival, recapture and abundance estimates were derived using a Cormack-Jolly-Seber modelling approach and a Horwitz-Thompson type abundance estimator. The best-fit model was a 2-ageclass Brownie-Robson type model that estimated apparent annual survival for the non-transient winter stopover ageclass at approximately 0.945 (95% confidence interval: 0.929–0.957). Apparent annual abundance of winter stopover humpback whales in Hervey Bay was estimated to have increased significantly over the past 21 years at ca. 13.4% per annum (95% CI 11.6–15.2). The most recent Hervey Bay winter stopover population (2007) was estimated to comprise ca. 6,246 post-yearlings (95% CI 5,011–7,482). This estimated rate of population increase is similar to estimates for other surveys along the east Australian coast but significantly higher than the intrinsic rate of increase (rmax) estimated recently for several recovering Southern Hemisphere humpback whale stocks based on the feeding ground sampling.